HEPATOPROTECTIVE POTENTIAL OF SAPINDUS MUKOROSSI AGAINST CCL4-INDUCED LIVER DAMAGE THROUGH REGULATION OF VOLTAGE DEPENDENT ANION CHANNEL EXPRESSION - MEESALA SRINIVASARAO,; HARITHA PASUPULATI,; MOHAMMED IBRAHIM, (International Journal of Pharma and Bio Sciences, 2016)
In liver diseases.(Voltage Dependent Anion Channel) VDAC had played an important role because it triggers the opening of the mitochondrial porin ion channel that leads to mitochondrial damage and induce apoptotic or necrotic hepatic cell death. In the present study, the relationship between expression of mitochondrial VDAC may underlie the protective effect of Sapindus mukorossi against carbon tetrachloride (CCl4) induced liver damage in Wister rats. The protective potential of total saponin fraction of Sapindus mukorossi was determined by evaluating Aminotransferase activity, mitochondrial membrane potential, calcium-induced liver MPT (Mitochondrial permeability transition) and VDAC expression. Saponin administration shows significant dose dependent restoration of serum enzymes levels. The membrane potential of mitochondria dropped from -199.1 ±4.4 mv to-157. 6±4.8mv after the rats has been treated with CCL4. Pretreatment with (S.mukorossi sapogenin fraction)SMSF showed significant preservation of mitochondrial membrane potential as compared to CCl4 control demonstrated the mitochondrial protection. It exerted a dose-dependent effect against sensitivity to mitochondrial swelling induced by calcium. SMSF (150 mg/kg) significantly increased the transcription and translation of VDAC. In conclusion the study suggests that Sapindus mukorossi significantly prevents the damage to liver mitochondria induced by CCl4 through regulating the expression of VDAC.